Unimolecular decay dynamics of Criegee intermediates: Energy-resolved rates, thermal rates, and their atmospheric impact. Issue 1 (2nd January 2020) - Stephenson, Thomas A.; Lester, Marsha I.
ABSTRACT: Criegee intermediates are reactive species formed in the ozonolysis of alkenes. Their subsequent chemistry is critical to an accounting of OH production, aerosol formation, and the oxidative capacity of the atmosphere. The fate of Criegee intermediates in the atmosphere is determined by the competition between bimolecular and unimolecular processes, so an understanding of unimolecular decay is an important topic in both atmospheric and physical chemistry. The unimolecular decay dynamics of Criegee intermediates is sensitive to the nature and conformation of its substituents. Multiple isomerisation pathways are possible, with some structures capable of a 1, 4-hydrogen transfer reaction that is efficient, and generally competes with bimolecular reactions. Experimental studies that provide energy-resolved rate constants (k(E)) offer benchmarks for RRKM calculations that can be extrapolated to thermal rate constants (k(T)) under atmospheric conditions. The comparison of k(E) and k(T) values among a series of homologous Criegee intermediates provides insights into the role of structure, energetics, and tunnelling in the unimolecular decay dynamics of these species. Alternative unimolecular decay pathways also illuminate aspects of the dynamics of Criegee intermediates. These pathways are less susceptible to tunnelling, may be slower or faster than hydrogen transfer processes, and thus more or less competitive with bimolecular reactions.